Henry and the clubhouse - Cleary, Beverly (Henry Huggins., 2017)
Fiery Ramona Quimby and the well-meaning Henry Huggins may clash, but in this delightful and hilariously told novel by Newbery Medal-winning author Beverly Cleary, an unlikely compromise wins the day. Henry and his friends are building a no-girls-allowed clubhouse. With a private space of their own away from everyone else and even a top-secret entry password they're all thrilled with their boy fort. But Henry's about to find out that nothing, not even a sign, will keep gutsy Ramona out of their clubhouse and her retaliation may just ruin Henry's newspaper career.